Komunikasi Resiliensi Ibu Tunggal dalam Meningkatkan Ketahanan Keluarga - Hakikoh, Heka Rizky; Hariyati, Farida; Corliana, Tellys (Unitri Press, 2025)
Being a single mother is a challenging reality that demands extraordinary resilience in facing various psychological, social, and economic pressures while adapting to new life circumstances. It is not easy for single mothers to remain strong in the face of life's challenges, as they must confront numerous pressures and difficult situations that require them to adapt. This condition makes resilience a highly necessary quality, yet one that is not easily attained by single mothers. Based on these issues, this study aims to understand how the three participants build their resilience after their divorces. Using a qualitative phenomenological approach, the researcher collected data through direct interviews, observations, and supporting documents. The findings reveal similar patterns among the three participants, showing that they successfully developed a more positive outlook on life, particularly through their work activities. Employment became an important means for them to rebuild their lives after divorce. Abstrak Menjadi ibu tunggal merupakan realitas yang menantang, menuntut ketahanan luar biasa dalam menghadapi beragam tekanan psikologis, sosial, dan ekonomi sambil beradaptasi dengan situasi hidup yang baru. Tidak mudah bagi ibu tunggal untuk tetap tangguh menghadapi tantangan hidup, mengingat mereka harus berhadapan dengan berbagai tekanan dan situasi sulit yang mengharuskan mereka beradaptasi. Kondisi ini menjadikan resiliensi sebagai kualitas yang sangat dibutuhkan namun tidak mudah dicapai oleh para ibu tunggal. Berdasarkan permasalahan, penelitian ini bertujuan memahami bagaimana kelima partisipan membangun ketahanan diri setelah perceraian mereka. Dengan menggunakan pendekatan kualitatif fenomenologi, peneliti mengumpulkan data melalui wawancara langsung, pengamatan, dan dokumen pendukung. Temuan penelitian mengungkapkan pola yang serupa di antara kelima partisipan, di mana mereka berhasil mengembangkan pandangan hidup yang lebih positif terutama melalui aktivitas pekerjaan. Proses bekerja menjadi sarana penting bagi mereka dalam membangun kembali kehidupan pasca perceraian.